Forestry and traditional woodland management in North Dalmatia c. 1790 to 1990: an environmental history - Tekic, Ivan (2019)
This thesis focuses on traditional management and forestry in coastal areas of northern Dalmatia in Croatia. It considers the time period from the dissolution of Republic of Venice until the end of SFR Yugoslavia in 1990. It is based on archival records on forestry activities, Austrian land surveys from the 1820s, oral histories in three case studies, aerial photographs and analysis of articles and discussions published in the Forestry Journal since 1877. The thesis is structured chronologically, and woodland use, policies and management are considered in the context of different administrations – the French (1805-1815), Austrian (1815-1918), first Yugoslav (1920-1941) and second Yugoslav (1945-1990). Although today they are neglected and considered unproductive, the research emphasises that traditional woodlands and wooded landscapes had a major role in the local livelihoods in the study area. It explores the ways these woodlands were used by local people and how they were shaped by woodland regulation and management which were characterised by strong continuity over the last two centuries. It also investigates how reforestation, the most important forestry policy in Dalmatia, developed in the late 19th century and its implications for land use and tourism.